Process Assurance Capability Analysis Based on Capability Process, Detection Process Capabilities and Irregular Condition Actions in Automotive Industry - Abid, Muhammad Miftahul; Wisudawati, Tri (Universitas Al Azhar Indonesia, 2025)
Rail roof side is an automotive product with high quality specifications. In the manufacturing process, there are unstable process issues that cause variations in size. On the other hand, the process abnormality detection system occurs at the end of the production process, so potential defects cannot be detected during the process. This study aims to ensure stable process quality so that defective products can be detected during the manufacturing process. The quality assurance process uses an approach based on process stability score, known as Cpk. The capability of process detection devices derived from the quality control technology used, and the ability to address irregular conditions identified through human capability to take action when process abnormalities occur. Based on the calculation of process quality assurance capability, a rank value of 1.70 indicates that the quality assurance system has been achieved. This means that the process assurance status is capable of preventing and detecting process variation issues and defects from the start of the process.Keywords – Assurance, Capability, Defect, Detection, Variation.